Ciclos limite em sistemas lineares suaves por parte - Silva, Ana Maria Alves da (2018)
In this work we will study limit cycles in piecewise smooth linear systems. We begin studying the case where the separation curve is a polygonal and we give an example of a system having seven limit cycles. The existence of an arbitrary number of limit cycles is also proved for these systems, as well as an example of a system with 10 limit cycles. The existence of n limit cycles, n 2 N, is also studied through a perturbation in the separation curve. Finally, we study limit cycles in planar piecewise linear systems presenting a twofold singularity in R2, as well as limit cycles sorrounding a T-singularity.